2014
DOI: 10.1136/bmj.g1572
|View full text |Cite
|
Sign up to set email alerts
|

Costs of minimum alcohol pricing would outweigh benefits

Abstract: Many people disagree with a minimum price on a unit of alcohol on grounds that are evidence based, writes Christopher Snowdon in response to the BMJ’s recent series by Jonathan Gornall

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…The IEA has long expressed opposition to MUP303132 and did so once again in an April article by Christopher Snowdon, its head of lifestyle economics. MUP, he wrote, was “a shamelessly paternalistic and patently regressive policy.…”
Section: Political Linksmentioning
confidence: 99%
“…The IEA has long expressed opposition to MUP303132 and did so once again in an April article by Christopher Snowdon, its head of lifestyle economics. MUP, he wrote, was “a shamelessly paternalistic and patently regressive policy.…”
Section: Political Linksmentioning
confidence: 99%
“…Subsequently it was revealed that the IEA is in receipt of funding from the alcohol and retail industries as well (Snowdon, 2014).…”
Section: Civil Societymentioning
confidence: 99%
“…Two examples indicate the difficulties. First the case of the IEA which 'has a policy of donor confidentiality' (Snowdon, 2014). In a contribution to the British Medical Journal (BMJ) admonishing the journal for publishing an account of the influence of the alcohol industry on government policy, the IEA head of 'lifestyle economics' , Christopher Snowdon declared only minor personal conflicts of interest.…”
Section: Transparency In Civil Societymentioning
confidence: 99%
“…medidas legislativas contra el tabaco y el alcohol 47,48 . La industria del alcohol es poderosa y cuenta con el apoyo de académi-cos poco escrupulosos.…”
Section: Tabla 4 Una Propuesta De Tareas Prioritarias Para El Movimieunclassified